GETTING ACTIVATED CARBON AND ESSENTIAL OIL FROM PEACH (BLANQUILLO) - Reyna M., Leoncio (2006)
In Peru peach varieties, which are sold in markets throughout the year occur. Mostly pulp but not seeds and bones of the seeds consumed. In this work the production of activated carbon from bones with a yield of 20% and an absorption rate of 50% is reported. The essential oil obtained from the seeds using ethanol as solvent. The product obtained proved to be of good quality with pe 180 ° C